2011
DOI: 10.1093/qjmed/hcq260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of critically ill cancer patients with septic shock

Abstract: The variables associated with increased mortality were the degree of organ dysfunction determined by SOFA score at ICU admission and PS≥2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…Majority of patients in the current study could not carry on self-care and were confined to bed completely. In agreement with the other studies,8 10 36 our analysis showed that patients with poor PS (≥3) had 5.4 times more risks of mortality. IMV was needed in 62 (62%) patients at ICU admission in the form of intubation (endotracheal tube (ETT)) or tracheostomy due to ARDS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Majority of patients in the current study could not carry on self-care and were confined to bed completely. In agreement with the other studies,8 10 36 our analysis showed that patients with poor PS (≥3) had 5.4 times more risks of mortality. IMV was needed in 62 (62%) patients at ICU admission in the form of intubation (endotracheal tube (ETT)) or tracheostomy due to ARDS.…”
Section: Discussionsupporting
confidence: 92%
“…Majority of the patients in the current study had solid tumour and these findings corroborate with previous study demonstrating increased association of solid tumour with PASS 15. Existing literature described significant relationship between septic shock at ICU admission and mortality 8 15. However, our findings are incongruous with results of previous investigations where septic shock at ICU admission was not associated (p=0.667) with mortality.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Mortality in ICU was 40% in cancer group, a number similar to that found by Ñamendys-Silva et al [26] in Mexico. In Brazil, Soares et al [18] reported a 44% of mortality rate in a cancer group admitted at ICU due to medical causes, not specifically to sepsis, which accounted only for 15% of admissions.…”
Section: Discussionsupporting
confidence: 88%
“…Our ICU routinely implements the guidelines for management of severe sepsis and septic shock [27, 28], because they have been associated with a significant reduction in hospital mortality in patients with severe sepsis and septic shock from 37% to 30.8% ( P = 0.001) [29]. …”
Section: Discussionmentioning
confidence: 99%